Enhancement of Biomimetic Enzymatic Mineralization of Gellan Gum Polysaccharide Hydrogels by Plant-Derived Gallotannins - Douglas, Timothy E L; Keppler, Julia K; Vandrovcová, Marta; Plencner, Martin; Beranová, Jana; Feuereisen, Michelle; Parakhonskiy, Bogdan V; Svenskaya, Yulia; Atkin, Vsevolod; Ivanova, Anna; Ricquier, Patrick; Balcaen, Lieve; et al. (International journal of molecular sciences, 2020)
Mineralization of hydrogel biomaterials with calcium phosphate (CaP) is considered advantageous for bone regeneration. Mineralization can be both induced by the enzyme alkaline phosphatase (ALP) and promoted by calcium-binding biomolecules, such as plant-derived polyphenols. In this study, ALP-loaded gellan gum (GG) hydrogels were enriched with gallotannins, a subclass of polyphenols. Five preparations were compared, namely three tannic acids of differing molecular weight (MW), pentagalloyl glucose (PGG), and a gallotannin-rich extract from mango kernel (Mangifera indica L.). Certain gallotannin preparations promoted mineralization to a greater degree than others. The various gallotannin preparations bound differently to ALP and influenced the size of aggregates of ALP, which may be related to ability to promote mineralization. Human osteoblast-like Saos-2 cells grew in eluate from mineralized hydrogels. Gallotannin incorporation impeded cell growth on hydrogels and did not impart antibacterial activity. In conclusion, gallotannin incorporation aided mineralization but reduced cytocompatibility.
Keywords: polyfenoly; Polysaccharides, Bacterial; lidé; Polysaccharides; Calcification, Physiologic; Biomimetics; Hydrolyzable Tannins; Biocompatible Materials; rostliny; polyphenol; antibakteriální látky; Calcium Phosphates; Hydrogels; minerály; alkalická fosfatasa; bakteriální polysacharidy; hydrolyzovatelné taniny; protein-polyphenol interaction; Polyphenols; composite; fyziologická kalcifikace; Humans; rostlinné extrakty; Anti-Bacterial Agents; hydrogely; Mangifera; regenerace kostí; biokompatibilní materiály; polysacharidy; Plants; Minerals; osteoblasty; Alkaline Phosphatase; Osteoblasts; Plant Extracts; enzyme; fosforečnany vápenaté; Bone Regeneration; gellan gum; mineralization; biomimetika